Optimization and characterization of antioxidant potential, in vitro protein digestion and structural attributes of microwave processed multigrain pasta. Issue 10 (22nd July 2019) - Kamble, Dinkar B.; Singh, Rakhi; Rani, Savita; Kaur, Barjinder Pal; Upadhyay, Ashutosh; Kumar, Nitin
Abstract: A central composite design was used to optimize flour combination consisting of sorghum flour (20%–35%), finger millet flour (10%–25%) and gluten (3%–5%) on five responses, namely cooking loss (CL), cooking time (CT), water absorption index (WAI), firmness, and overall acceptability (OA) of multigrain pasta. The optimized pasta was evaluated for physicochemical, antioxidant/anti‐nutritional, in vitro protein digestibility (IVPD), and structural attributes. Optimum level for sorghum, finger millet, and gluten were 31.96%, 13.04%, and 3.40%, respectively, resulted in CL = 9.69 ± 0.44%, CT = 6.10 ± 0.05 min, WAI = 119.54 ± 2.54%, firmness = 11.05 ± 2.40 N, and OA = 7.30 ± 0.20. The antioxidant analysis showed higher in 1, 1‐diphenyl‐2‐picrylhydrazyl activity, ferric reducing power and (2, 2‐azino‐bis‐3‐ethylbenzothiazoline‐6‐sulfonic acid) activity of optimized pasta. IVPD of optimized pasta (76.51%) altered significantly compared to control pasta (89.69%). However, FTIR and XRD pattern revealed a similar secondary structure for both types of pasta. Practical applications: The growing interest toward consumption of nutritionally enriched healthy foods has promoted the cereal industry toward formulations of millet‐based products. However, the quality characteristics of both sorghum and finger millet‐based pasta have been poorly investigated. Higher total phenolic content and antioxidant activity suggested that both sorghum and finger millet could be used to make the pasta having numerous health benefits. Findings of this work may promote the effective utilization of multigrain flour in pasta or other food products which further offer the advantages of a reduced burden on traditional crops, inspiring the agriculture produce and lessen the cost of the final product.